Zinc ions in ear, nose, and throat work. - Friel, Alfred Richard (J. Wright, 1948)
Zinc Ions in Ear, Nose, and Throat Work presents the method of effectively treating otorrhea. This three-chapter text discusses the means of applying electric current to the infected area to introduce zinc ions into the tissue. It addresses the progress made with the treatment and the use of this in treating maxillary and frontal sinusitis. Some of the topics covered in the book are the dissociation of atoms into ions; description of a simple voltaic cell; features and chemical reactions in an electrolytic cell; and source and regulation of the electric current. The next chapter provides the b.